Age-Dependent Up-Regulation of HCN Channels in Spiral Ganglion Neurons Coincide With Hearing Loss in Mice - Shen, Haitao; Liu, Weilin; Geng, Qiaowei; Li, Hongchen; Lu, Mingshun; Liang, Peng; Zhang, Bo; Yamoah, Ebenezer N.; Lv, Ping (Frontiers in Aging Neuroscience, 2018)
Age-related hearing loss (AHL) is the most common sensory disorder in the elderly population. Dysfunction of spiral ganglion neurons (SGNs) is a major contributor to AHL. Previously, we showed that one of the changes in the aging auditory system is SGN excitability increase in mice (i.e., AHL mice) compared with young ones, which raised the possibility that the excitability changes in SGNs may contribute to AHL. Since hyperpolarization-activated cyclic nucleotide-gated (HCN) channels play important roles in determining neuronal excitability, we predicted that HCN channels in SGNs are involved in AHL. To investigate the contribution of HCN channels to AHL, we examined the expression and biophysical properties of HCN channels in SGNs from post-hearing adult and one-year old mice during hearing loss. We report that a dramatic increase of HCN channel current (Ih) in SGNs from old mice (one-year old) was associated with increased expression of HCN1 and HCN2 subunits, suggesting that upregulation of HCN channels in SGNs is one of the important facets of AHL. Moreover, Ih produced a major impact on resting membrane potential and firing properties of SGNs from old mice, indicating that upregulation of Ih may contribute to AHL by regulating SGN excitability. Additionally, AIF-mediated apoptosis in SGNs was observed in old mice and activation of HCN channels induced AIF activation. Thus, this study demonstrates that HCN channels contribute to AHL by altering SGN function and inducing apoptosis in SGNs from old mice.